An evolving approach to the laboratory assessment of COVID‐19 - Lu, Hongzhou; Stratton, Charles W.; Tang, Yi‐Wei (Journal of medical virology, 2020)
As the 2019 novel coronavirus disease (COVID‐19) outbreak has evolved in each country, the approach to the laboratory assessment of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection has had to evolve as well. This review addresses the evolving approach to the laboratory assessment of COVID‐19 and discusses how algorithms for testing have been driven, in part, by the demand for testing overwhelming the capacity to accomplish such testing. This review focused on testing in the USA, as this testing is evolving, whereas in China and other countries such as South Korea testing is widely available and includes both molecular testing for SARS‐CoV‐2 as well as serological testing using both enzyme‐linked immunosorbent assay methodology and lateral flow immunoassay methodology. Although commercial testing systems are becoming available, there will likely be insufficient numbers of such tests due to high demand. Serological testing will be the next testing issue as the COVID‐19 begins to subside. This will allow immunity testing as well as will allow the parameters of the COVID‐19 outbreak to be defined.